URGENSI MICROLEARNING DALAM UPAYA EFEKTIFITAS PEMBELAJARAN SISWA DI MTS AL – AMIRIYYAH - Denny Bhekti Kurnianto; Imam Khaudli (CV. ADIBA AISHA AMIRA, 2025)
This study aims to analyze the eflectiveness of microlearning strategies in improving the quality and efficiency of the learning process in the digital era. The background of this study is based on social changes and learning behavior patterns of modern society that are increasingly dynamic, fast, and dependent on technology. This study uses a descriptive qualitative approach with the object of research MTs Al-Amiriyyah, a madrasah that has integrated technology into its learning process. Data were collected through interviews, observations, and documentation. The results of the study showed that microlearning strategies were able to significantly increase focus, material retention, and student cognitive involvement. then analyzed using thematic analysis methods. from this study lies in a holistic approach that not only assesses microlearning from the technical side of learning, but also as a social response to the dynamics of modern society's learning culture.